Heritabilitas, Sumber Gen, Dan Durabilitas Ketahanan Varietas Padi Terhadap Penyakit Hawar Daun Bakteri - Dini Yuliani; Wage Ratna Rohaeni (Badan Penelitian dan Pengembangan Pertanian, 2017)
Bacterial leaf blight (BLB) disease is one of the obstacles in increasing of rice production. The use of resistant varieties is an effective and easy to implement for farmers. This paper discusses the heritability and source of resistance genes of rice varieties against the BLB disease and strategies to maintain the durability of resistant varieties as one of the control efforts through plant breeding to supports the increasing of rice production. Assembling and development of resistant varieties play an important role in controlling BLB disease because it has a genetic resistancemechanism that can be inherited to progeny level. Varieties with vertical resistance are easily broken by pathogens, so it is necessary to assembling of varieties with horizontal resistance. To obtain the resistant progeny to BLB disease in the assembly of varieties, the position of the resistant varieties should be played as a female parent that has a high specific joining power. The nature of resistance to BLB is from a population whose parent genes are derived from multiple cross results has higher heritability. The populations derived from a double-cross have multigenic resistance and have the potential to produce recombinant individuals resistant for prolonged periods (durable). The availability of durable resistant varieties become a key requirement in sustainable BLB disease control. This matter can be done by improving the resistance of varieties through the assembling of varieties with various sources of resistance such as wild rice, local rice, and introduced rice.Keywords: Rice, varieties, resistance, bacterial leaf blight, durability, heritability ABSTRAKPenyakit hawar daun bakteri (HDB) merupakan salah satu kendala dalam peningkatan produksi padi. Penggunaan varietas tahan merupakan cara pengendalian yang efektif dan mudah diterapkan petani. Tulisan ini membahas heritabilitas dan sumber gen ketahanan varietas padi terhadap penyakit HDB dan strategi mempertahankan durabilitas varietas tahan sebagai salah satu upaya pengendalian melalui pemuliaan tanaman mendukung upaya peningkatan produksi padi. Perakitan dan pengembangan varietas tahan berperan penting mengendalikan penyakit HDB, karena memiliki mekanisme ketahanan genetik yang dapat diwariskan kepada keturunannya. Varietas dengan ketahanan vertikal mudah dipatahkan oleh patogen, sehingga perlu upaya perakitan varietas dengan ketahanan horizontal. Untuk memperoleh keturunan tanaman padi yang tahan terhadap penyakit HDB dalam perakitan varietas, posisi tetua tahan sebaiknya diperankan sebagai tetua betina yang memiliki daya gabung khusus yang tinggi. Sifat ketahanan HDB dari populasi tetua yang mengandung gen dari hasil silang ganda memilliki heritabilitas lebih tinggi. Populasi turunan dari silang ganda memiliki ketahanan multigenik dan berpeluang menghasilkan individu rekombinan tahan untuk periode yang lama (durable). Ketersediaan varietas tahan yang durable menjadi syarat utama dalam pengendalian penyakit HDB secara berkelanjutan. Hal ini dapat dilakukan dengan perbaikan ketahanan varietas melalui perakitan varietas dengan berbagai sumber ketahanan, di antaranya padi liar, padi lokal, dan padi introduksi.Kata kunci: Padi, varietas, ketahanan, hawar daun bakteri, durabilitas, heritabilitas